Quality of Life Assessment in Palliative Stage Cancer Patients - -, Maria; -, Witjaksono (Indonesian Journal of Cancer, 2007)
Indicators of success in oncology traditionally include cure, survival, and tumor response. In advanced stage however, Quality of life (QOL) has become an important outcomes.2012 Despite the broad use of the term QOL, it is difficult precisely define.1012 It is multidimensional, dynamic and subjective concept.3510 The numerous questionnaire for QOL measurement lead to a challenge for its application.12 Most of QOL instrument include physical symptoms, functioning, psychological and social well-being.12 In advanced stage existential, meaning, fulfillment, purpose and grief become more prominent.1112 Besides the contain of the questionnaire, validity and reliability need to be considered in deciding which instrument will be applied.12This paper discusses the definition of QOL, the purpose of measuring QOL, various QOL instruments, the McGill Quality of Life Questionnaire as a measure suggested in clinical practice and the reasons for its application.Key words; Quality of Life, Palliative, Cancer Patients